VD_FINDINFO Jug / 2024 / 538 vom 1. Januar 2021 - VD Tribunal cantonal (2021)
EMPLOYÉ PUBLIC, ENSEIGNANT, RÉSILIATION IMMÉDIATE, JUSTE MOTIF, TORT MORAL | 337c al. 1 CO, 337c al. 3 CO, 49 CO, 59 al. 1 LPers-VD, 61 LPers-VD